Boardroom female participation, intellectual capital efficiency and firm performance in developing countries: Evidence from Nigeria. Issue 50 (13th April 2020) - Isola, Wakeel Atanda; Adeleye, Bosede Ngozi; Olohunlana, Aminat Olayinka
Abstract : Purpose: This paper aims to focus on the implications of female participation in the board on the management of intellectual capital for improved firm performance, particularly in the Nigerian-banking sector. It uses the resource dependency theory to ascertain the link between female board participation, intellectual capital and performances. Design/methodology/approach: The paper adopted longitudinal panel analysis to analyze data obtained from the annual reports of selected listed commercial banks in Nigeria. The random effect regression was adopted as the method of analysis. The decision was informed by conducting the Hausman test. Findings: The results revealed that female board participation has insignificant influence on bank performances, whereas intellectual capital efficiencies positively contribute to bank performances. However, significant influences were exhibited upon the interactions of female board participation and components of intellectual capital efficiency on bank performances. Research limitations/implications: Because of the focus of the research work, which is centered on the banking sector of the Nigerian economy, the findings of the research may not be sufficiently suitable for other sectors of the country. This, however, leaves the coast for other researchers to extend research on intellectual capital and gender participation to other non-financial sectors and other countries. Practical implications: The outcome implies that there is a need for increased female participation in the boardroom to harness optimal intellectual capital efficiencies for firm performance. It further confirmed that intellectual capital unlocks the hidden treasure of firms. Originality/value: The paper identifies and fulfills a niche on the need to extend the frontier of knowledge on intellectual capital and gender equity.